Safety of intravenous immunoglobulin treatment. - Atrah, H I (1985)
In a prospective clinical and biochemical study of 16 patients treated with high doses of an immunoglobulin product that had been modified for intravenous use by mild pepsin treatment at pH 4 no evidence of hepatitis could be found. This contrasts with recent reports that intravenous immunoglobulin products can apparently transmit non-A, non-B hepatitis.